1991
DOI: 10.1152/ajpendo.1991.261.4.e430
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic phase insulin release in normal weight males: verification and reliability

Abstract: The existence and reliability of cephalic phase insulin release (CPIR) were tested in 20 normal weight males. Each subject was challenged three times with the same food stimulus over a 5-day period. Four baseline blood samples were taken at 5-min intervals before food ingestion and then every 2 min for 16 min postingestion. Significant increases in plasma insulin were found at 4 min postingestion on each trial day. CPIR was found to be highly reproducible between trials (r = 0.83; P less than 0.001). Fifty per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
96
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 24 publications
7
96
0
Order By: Relevance
“…Because Rodriguez-Diaz et al found sympathetic neurovascular contacts in human islets, they proceeded to emphasise species differences in innervation patterns. Our data, however, support species similarities in the innervation pattern: both mouse and human islets displayed a sympathetic neurovascular complex in the core, which is in line with the similar effect of autonomic activation on islet hormone release in animals and humans [3,10,[31][32][33][34].…”
Section: Discussionsupporting
confidence: 84%
“…Because Rodriguez-Diaz et al found sympathetic neurovascular contacts in human islets, they proceeded to emphasise species differences in innervation patterns. Our data, however, support species similarities in the innervation pattern: both mouse and human islets displayed a sympathetic neurovascular complex in the core, which is in line with the similar effect of autonomic activation on islet hormone release in animals and humans [3,10,[31][32][33][34].…”
Section: Discussionsupporting
confidence: 84%
“…A cephalic phase that is induced by sensory stimulation in the oral cavity and is involved in the regulation of insulin secretion after meal ingestion in humans has been demonstrated in several previous reports (3,5,(7)(8)(9)(10)33,34). Because atropine reduces the cephalic phase insulin release, it has been thought that cholinergic mechanisms may contribute (10).…”
Section: Discussionmentioning
confidence: 90%
“…he preabsorptive or cephalic phase insulin response, which lasts for ϳ10 min, is initiated by meal ingestion, as has been demonstrated in humans and rats (1)(2)(3)(4)(5)(6)(7)(8)(9). It is abolished by vagotomy in rats (1) and by atropine in rats (1) and humans (10), suggesting mediation by cholinergic mechanisms.…”
mentioning
confidence: 84%
“…For example, an initial pulse of insulin secretion in response to food ingestion occurs within ten minutes (peak value at 4 minutes post ingestion) in normal weight men, and this is before any change in blood glucose concentration due to absorption of nutrients could occur (Teff et al, 1991). The cephalic phase insulin response can also be triggered by non-nutritive sweet tasting substances, such as saccharin (Powley and Berthoud, 1985).…”
Section: Evidence For Cephalic Phase Responsesmentioning
confidence: 99%